2022
DOI: 10.1007/s00376-022-1439-1
|View full text |Cite
|
Sign up to set email alerts
|

The Super-large Ensemble Experiments of CAS FGOALS-g3

Abstract: A super-large ensemble simulation dataset with 110 members has been produced by the fully coupled model FGOALS-g3 developed by researchers at the Institute of Atmospheric Physics, Chinese Academy of Sciences. This is the first dataset of large ensemble simulations with a climate system model developed by a Chinese modeling center. The simulation has the largest realizations up to now worldwide in terms of single-model initial-condition large ensembles. Each member includes a historical experiment (1850–2014) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…There are 30 vertical levels for the ocean model component. The horizontal resolution of FGOALS-g3 used for the super-large ensemble is comparable to other CMIP6 models with large ensembles, coarser than that of CESM2, and finer than that of CanESM5 (Lin et al, 2022).…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…There are 30 vertical levels for the ocean model component. The horizontal resolution of FGOALS-g3 used for the super-large ensemble is comparable to other CMIP6 models with large ensembles, coarser than that of CESM2, and finer than that of CanESM5 (Lin et al, 2022).…”
Section: Methodsmentioning
confidence: 78%
“…The super‐large ensemble has been proven to be capable of reproducing the historical evolution of average SAT and land precipitation over the globe well during 1850–2014. The large‐scale spatial features of SAT are well simulated, and the ensemble can reproduce the Asian monsoonal circulation and associated precipitation (Lin et al, 2022). Therefore, we can use this ensemble dataset to explore the change in the connections of the summertime NWPSA to the preceding ENSO under global warming.…”
Section: Methodsmentioning
confidence: 99%
“…The impact of aerosols on ENSO amplitude is also detectable in MIROC6. However, it is still challenging to distinguish these changes between high-emission scenarios or between low-emission scenarios, implying the importance of implementing spatiotemporal analysis methods (e.g., Wills et al, 2020) or generating larger ensembles (e.g., Maher et al, 2019;Rodgers et al, 2021;Lin et al, 2022). The mechanisms underlying the clearly detected changes in this study and the changes in other internal variability will be reported in future works.…”
Section: Changes In Internal Variabilitymentioning
confidence: 85%
“…The Swedish Meteorological and Hydrological Institute used the EC-Earth3 model to generate 50-member ensembles over the historical interval and four shared socioeconomic pathway simulations (2015-2100; SSP1-1.9, SSP3-3.4, SSP5-3.4-OS, and SSP5-8.5) (SMHI-LENS; Wyser et al, 2021). Lin et al (2022) computed 110-member ensemble simulations for the historical period and SSP5-8.5 scenario using the FGOALS-g3 CGCM.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these SMILEs are listed in the Multi‐Model Large Ensemble Archive (https://www.cesm.ucar.edu/community-projects/mmlea; Deser et al., 2020). Next to MPI‐GE CMIP6, currently available SMILEs with CMIP6 forcing and at least 30 realizations for both the historical and future period are ACCESS‐ESM1.5 (Ziehn et al., 2020), CanESM5 (Swart et al., 2019), FGOALS (Lin et al., 2022), LENS2 (Rodgers et al., 2021), SMHI‐LENS (Wyser et al., 2021), SPEAR‐MED (Delworth et al., 2020), and MIROC6 (Tatebe et al., 2019). In comparison to the other CMIP6 SMILEs, MPI‐GE CMIP6 provides the most extensive high‐frequency output for the historical period and five different emission scenarios (Table 1).…”
Section: Introductionmentioning
confidence: 99%